Ethical Landscape of Advertising in Pakistan: Analyzing the Sprite Advertisements from 2016 to 2023 - Ibrar, Zahid; Muhammad Riaz; Muhammad Rashid (Journal of Peace, Development and Communication, 2024)
This article explored the ethical issues raised in Pakistani Sprite commercials during the previous eight years. It investigated how cultural values and societal standards are reflected in and may be influenced by these commercials. The article used qualitative content analysis to examine the data from Sprite’s official advertisements, which were broadcast in Pakistan between 2016 and 2023. The article used a set of analysis filters that the researcher constructed, concentrating on the language style, social and cultural themes, and demographic traits of the advertisement characters in the context of Pakistani society and culture. The results showed that Sprite’s advertising tactics changed significantly throughout the eight years. The article emphasized how important it is for marketers to balance their audience’s cultural and ethical values and business goals.